IOb-Cache: a high-performance configurable open-source cache - Roque, João, V. (2021)
sorts of open-source implementations of peripherals and other system-on-chip modules. Despite the recent advent of open-source hardware, the available open-source caches have low configurability, limited lack of support for single-cycle pipelined memory accesses, and use non-standard hardware interfaces. In this paper, the IObundle cache (IOb-Cache), a high-performance configurable open-source cache is proposed, developed and deployed. The cache has front-end and back-end modules for fast integration with processors and memory controllers. The front-end module supports the native interface, and the back-end module supports the native interface and the standard Advanced eXtensible Interface (AXI). The cache is highly configurable in structure and access policies. The back-end can be configured to read bursts of multiple words per transfer to take advantage of the available memory bandwidth. To the best of our knowledge, IOb-Cache is currently the only configurable cache that supports pipelined Central Processing Unit (CPU) interfaces and AXI memory bus interface. Additionally, it has a write-through buffer and an independent controller for fast, most of the time 1-cycle writing together with 1-cycle reading, while previous works only support 1-cycle reading. This allows the best clocks-per-Instruction (CPI) to be close to one (1.055). IOb-Cache is integrated into IOb System-on-Chip (IOb-SoC) Github repository, which has 29 stars and is already being used in 50 projects (forks).